Local and systemic effects of co‐stimulatory blockade using cytotoxic T lymphocyte antigen‐4‐immunoglobulin in dinitrofluorobenzene‐ and oxazolone‐induced contact hypersensitivity in mice. (3rd January 2013) - Christensen, A. D.; Skov, S.; Haase, C.
Summary Cytotoxic T lymphocyte‐associated antigen‐4 (CTLA‐4)‐immunoglobulin (Ig) has immunosuppressive properties both in vivo and in vitro, but much is still unknown about the mechanisms by which CTLA‐4‐Ig exerts its immunosuppressive activities in vivo. The aim of this study was to investigate the effect of CTLA‐4‐Ig in a mouse model of contact hypersensitivity (CHS). The inflammatory response in the presence or absence of CTLA‐4‐Ig was evaluated by measuring the increase in ear thickness in sensitized animals after challenge. We observed a dose‐dependent suppression of the ear swelling in both dinitrofluorobenzene (DNFB)‐ and oxazolone‐induced CHS. The suppressive effect was still present 3 weeks after administration, even in the absence of circulating levels of CTLA‐4‐Ig. It was further shown that CTLA‐4‐Ig inhibits activation of T cells in the draining lymph node after sensitization and affects the maturation level of both dendritic cells and B cells. Furthermore, CTLA‐4‐Ig reduces infiltration of activated CD8+ T cells into the inflamed ear tissue and suppresses both local and systemic inflammation, as illustrated by reduced expression of cytokines and chemokines in the inflamed ear and a reduced level of acute‐phase proteins in circulation. Finally, our results suggest that CTLA‐4‐Ig has a mainly immunosuppressive effect during the sensitization phase. We conclude that CTLA‐4‐Ig induces long‐term immunosuppression of both DNFB‐ and oxazolone‐induced inflammation and our data are the first to compare the effect of this compound in both DNFB‐ and oxazolone‐induced CHS and to show that CTLA‐4‐Ig exerts an immunosuppressive effect on both local and systemic inflammatory mediators which is mediated principally during the sensitization phase.